Chocolate with a purpose: Tony’s Chocolonely and ethically sustainable practices - van Zanten, Ynzo (Henry Stewart Talks, 2021)
Tony’s Chocolonely (company), Child slavery in Africa, Create awareness, Lead by example, Inspire to act